Consecutive Case Series of Healed Single-Molar Sites Immediately Restored with Wide-Diameter Implants: A 1-Year Evaluation - Hadi Antoun; Pierre Cherfane; Bouchra Sojod (International Journal of Dentistry)
Introduction. To evaluate outcomes of wide-diameter (6 mm) implants immediately provisionalized with cement-retained single crowns in posterior molar sites. Materials and Methods. Forty-eight consecutive patients received a total of 53 moderately rough-surface, 6 mm diameter implants in healed sites. All implants were immediately provisionalized with a cement-retained provisional crown. Final prosthesis with cement-retained porcelain fused to metal crowns was delivered 3–6 months later. Patients were followed up for 1 year. Outcome measures were implant failures and success rate, complications, marginal bone levels, bone level changes, papilla index, bleeding on probing, and inflammation. Results. One patient was lost to follow-up. At one year, the implant survival and success rate were 98.1%. The mean marginal bone loss after 1 year was −0.17±1.84 mm. Ideal papilla score was recorded at 83.8% of the sites. More than 95.6% of the sites showed no bleeding or inflammation. No procedure-related or device-related adverse events were reported. Conclusion. Wide-diameter (6 mm) implants can safely and successfully replace single posterior molars. Longer follow-up studies are necessary to evaluate the long-term success of these implants.